PET/CT imaging of NSCLC with a αvβ6 integrin-targeting peptide - Flechsig, Paul; Lindner, Thomas; Loktev, Anastasia; Mier, Walter; Sauter, Max; Meister, Michael; Herold-Mende, Christel; Haberkorn, Uwe; Altmann, Annette (Molecular imaging & biology, 2019)
PurposeTargeted therapies are regarded as promising approaches to increase 5-year survival rate of non-small cell lung cancer (NSCLC) patients. Here, we investigated the clinical value of the αvβ6 integrin-specific peptide SFITGv6 as a diagnostic reagent targeting NSCLC.MethodsAffinity and binding properties of [125I]SFITGv6 or [177Lu]SFITGv6 for αvβ6 integrin-expressing NSCLC cell lines were evaluated in cell culture experiments including competition, kinetic, internalization, and efflux. To confirm αvβ6 integrin specificity in vivo small-animal positron emission tomography (PET) imaging using [68Ga]SFITGv6 as radiotracer and biodistribution of [177Lu]SFITGv6 in NCI-H2009 and NCI-H322 tumor-bearing mice was performed. Finally, to distinguish between benign and malignant lesions [68Ga]SFITGv6 was applied as radiotracer for PET/x-ray computed tomography (CT) imaging of NSCLC patients with unclear diagnosis upon routinely performed 2-deoxy-2-[18F]flouro-D-glucose ([18F]FDG)-PET/CT. The biodistribution of the SFITGv6-ligand in different organs and tumor lesions of NSCLC patients was quantified 1 h and 3 h after injection measuring standard uptake values (SUV)max.ResultsIn vitro experiments revealed a significant time-dependent SFITGv6 binding of up to 33 % to αvβ6 integrin-expressing the cell lines NCI-H2009, NCI-H322, NCI-H292, NCI-H358, and high affinity (IC50-mean 3.1 nM) to NCI-H2009 and NCI-H322. Moreover, a fast internalization of approximately 66 % by NCI-H2009 and NCI-H322 cells was observed. Small-animal PET imaging and biodistribution experiments of NCI-H2009 and NCI-H322 xenografts demonstrated an increased tumor-specific accumulation of SFITGv6 40 to 60 min after injection. Finally, PET/CT scans of NSCLC patients after [18F] FDG injection followed by [68Ga]SFITGv6 application revealed correlating images. Comparing the uptake of [68Ga]SFITGv6 and [18F] FDG both PET/CT-examinations presented with significantly increased SUVmax values in histologically proven NSCLC lesions, but a generally higher accumulation of [18F] FDG was noticed.ConclusionsEven if SFITGv6 demonstrates excellent affinity and specificity for αvβ6 integrin-expressing NSCLC cell lines and several NSCLC xenografts [18F]FDG-PET/CT provides an advantage over [68Ga]SFITGv6-PET/CT for the diagnosis of NSCLC patients.
Gesehen am 05.11.2019